Implementasi Pembiayaan Mudharabah Pada Baitul Maal Wat Tamwil (BMT) Ummat Sengkang Dalam Perspektif Ekonomi Islam - Nurul Mawaddah; Idris Parakkasi; Muslihati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the mechanism of mudharabah financing at BMT Ummat Sengkang from an Islamic economic perspective. This study uses qualitative research with a phenomenological approach. The data sources used are primary data and secondary data where the data is obtained directly from the main source, while the data is obtained through interviews, observations, and documentation. The results of the study indicate that the mudharabah financing mechanism at BMT Ummat Sengkang is in accordance with the provisions of fatwa No. 7 / DSN-MUI / IV / 2000 concerning the pillars and conditions of mudharabah and in its transactions it reflects the principles of sharia which do not contain usury, gharar, and maysir. However, mudharabah financing at BMT Ummat Sengkang still needs to be improved by providing convenience in submitting financing.